2014
DOI: 10.1501/vetfak_0000002642
|View full text |Cite
|
Sign up to set email alerts
|

Köpeklerde kene kaynaklı bazı protozoon ve rickettsial enfeksiyonların Real Time PCR ile araştırılması ve saptanan izolatların moleküler karakterizasyonları

DÜZLÜ Önder; İNCİ

Abstract: Özet: Bu canis vogeli ve B. gibsoni izolatlarının 18S rRNA gen bölgesine ait sekanslarının dünyadaki aynı türden diğer izolatlarla ikili kıyaslamalarında %1,4±0,2, %0,3±0,2 ve %0,9±0,3 genetik farklılık saptanmıştır. E. canis için 16S rRNA gen bölgesi yönünden üç izolatın kendi aralarında %100 identik olduğu, dünyadaki izolatlarla ise %0,1 farklılık gösterdiği; A. phagocytophilum için ankA gen bölgesi yönünden üç izolatın kendi aralarında %99,8±0,2 identik olduğu, dünyadaki izolatlarla ise %0,9±0,3 farklılık… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Recent studies reported the presence of A. phagocytophilum nucleic acids in sheep [24,25] , in goats [25] in ixodid ticks [26][27][28] , in cattle [24,29,30] and in dogs [31] , as well as A. ovis in sheep [25] , in goats [25] and in ixodid ticks [28,32] in discrete regions. In East Black Sea region of Turkey, A. phagocytophilum seroprevalence by IFAT has been observed 14.86% (107/720) and specific DNA ratio by nested PCR has been found 12.35% (22/178) in sheep [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported the presence of A. phagocytophilum nucleic acids in sheep [24,25] , in goats [25] in ixodid ticks [26][27][28] , in cattle [24,29,30] and in dogs [31] , as well as A. ovis in sheep [25] , in goats [25] and in ixodid ticks [28,32] in discrete regions. In East Black Sea region of Turkey, A. phagocytophilum seroprevalence by IFAT has been observed 14.86% (107/720) and specific DNA ratio by nested PCR has been found 12.35% (22/178) in sheep [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Given that sequence data was available only from selected samples and employed for confirmatiory purposes, a thorough analysis of A. phagocytophilum sequence variations was not possible. Limited divergence was reported from various targets such as 16S rRNA and ankA sequences from Turkey [25,31] . So far, Anaplasma infections in small ruminants have not been documented in Thrace region of Turkey.…”
Section: Discussionmentioning
confidence: 99%